Covariabilidad entre la temperatura superficial del mar y el estrés de viento enlas escalas temporales estacional e interanual mediante observaciones satelitales frente a Perú - Alburqueque, Edward (2025)
Mesoscale ocean-atmosphere interaction between sea surface temperature (SST) and wind stress was investigated using 14 years (2008-2021) of ASCAT and OSTIA satellite observations. The study area was defined between the coastline and 200 nautical miles offshore, and between latitudes 3°S and 18°S. To quantify spatial and temporal variability in the strength of the interaction, binned scatterplots were constructed, and coupling coefficients were calculated between crosswind SST gradients and wind stress curl and between downwind SST gradients and wind stress divergence. The analysis reveals a strong seasonal variability in the strength of the coupling (77 % of the total variance), peaking during the summer and fall. Interannual variability is comparatively lower (6.6 % of the total variance). Finally, the method of Singular Value Decomposition (SVD) of coupled fields was applied, extracting spatial and temporal patterns of seasonal and interannual variability. The power spectrum of the interannual pattern exhibited two coupling peaks at 3.5 and 7 years.